Female sterility in Ulmus minor (Ulmaceae): a hypothesis invoking the cost of sex in a clonal plant. - López-Almansa, J; Pannell, J; Gil, L (2003)
A high incidence of individuals with low seed set was found in two populations of the field elm Ulmus minor, a European tree that reproduces sexually and via vegetative propagation through root sprouting. One population was a seminatural stand, while the other was established by artificial propagation of genotypes sampled widely across Spain. The low seed set in both populations was due to both pre- and post-zygotic factors, the importance of which vary between genotypes. These factors included gynoecial malformations that produced a non-ovulated pistil, early gynoecial necrosis (i.e., necrosis before any opportunities for pollination), and seed abortion. Female sterility gave rise to two classes of individuals: trees that were largely female-sterile but dispersed normal quantities of viable pollen, and trees that dispersed both normal pollen and substantial numbers of seeds. Reduced production of protein-rich seeds may increase the resource availability for clonal propagation, helping to maintain female-sterile individuals with hermaphrodites.